Biologics and Bronchial Thermoplasty for severe refractory asthma treatment: From eligibility criteria to real practice. A cross-sectional study. (February 2020) - Menzella, Francesco; Galeone, Carla; Ruggiero, Patrizia; Bagnasco, Diego; Catellani, Chiara; Facciolongo, Nicola
Abstract: The increasing knowledge on immuno-inflammatory pathways allowed the development of new therapeutic options in the field of severe refractory asthma (SRA). It is therefore very important to accurately identify phenotypes and endotypes of patients potentially eligible for innovative treatments. The aim of this study was to describe a cohort of patients affected by SRA referring to the Pneumology Unit of Azienda USL di Reggio Emilia/IRCCS in Reggio Emilia, Italy. It is an observational cross-sectional study, investigating the proportion of subjects with eligibility criteria for biological treatments (omalizumab, mepolizumab, benralizumab) and non-pharmacological treatment (bronchial thermoplasty, BT). We enrolled 137 patients with SRA referring to the centre from June 1st, 2017 to June 30th, 2019. The results of this study showed that 125 (91%) of patients were eligible for at least one biologic and 94 (69%) were eligible for BT. Only 6 (4%) of patients had no criteria for any available SRA treatments. Among biologics, there were only 11 (8%) patients resulting in overlap between omalizumab, mepolizumab and benralizumab, and 22 (16%) overlap of patients when BT was included. Considering eligibility criteria for BT, only 6 (4%) patients had inclusion criteria for BT, instead in real life 28% of patients were treated with BT. The major comorbidities were: bronchiectasis, chronic rhinosinusitis with nasal polyps (CRSwNP), gastro-esophageal reflux disease (GERD), and eosinophilic granulomatosis with polyangiitis (EGPA). The prevalence of bronchiectasis was much higher in the mepolizumab (45%) and benralizumab (43%) groups than in omalizumab (1%) and BT (7%), p < 0, 001; CRSwNP and GERD were equally present and EGPA was only present in the mepolizumab group. Overall, our population was eligible for biologicals in almost all cases, and a significant percentage of patients showed the presence of an overlap of allergic and eosinophilic endotypes. This implies the possibility of different therapeutic options and reiterates the need for a correct characterization of patients. This study confirmed how the identification of inflammatory endotypes and phenotypes represent a key role in the selection of the right therapy for the right patient.